Characterization of the Mahr Concept in Turkish and German International Private Laws - PÜRSELİM ARNİNG, HATİCE SELİN (My University, 2022)
Mahr, an Islamic law concept, has not been defined as a legal concept in Turkish and German laws. However, in both countries, courts occasionally have to deal with lawsuits regarding mahr. In Germany, mahr-related claims are made either by foreigners living in the country or by German citizens with an immigration background. In Turkey, such claims are set forward by Turkish citizens. It is also likely that some of these mahr-related lawsuits may involve a foreign element. In order to determine the law applicable to these claims, the court firstly needs to correctly characterize the concept with regards to conflict of laws. This article firstly explains the concept of mahr and afterwards discusses why the most suitable characterization is within the scope of the general provisions of marriage.

İslam hukukuna ait bir kavram olan mehir, Türk ve Alman hukuklarında tanımlanmamıştır. Ancak mehire ilişkin uyuşmazlıklar iki ülkenin de mahkemelerinde görülen davaların konusunu oluşturabilmektedir. Alman mahkemelerinde mehire ilişkin davalar, Almanya’da yaşayan yabancılar veya Alman vatandaşı olmakla birlikte Almanya’ya göç yollarıyla gelmiş kişiler tarafından açılmaktadır. Türkiye’de ise mehire ilişkin talepler, Türk vatandaşları tarafından ileri sürülebilmektedir. Mehire ilişkin uyuşmazlıkların yabancılık unsuru içermesi ihtimal dâhilindedir. Mehire ilişkin yabancılık unsuru içeren uyuşmazlıklarda, mahkemenin uygulanacak hukuku tespit edilebilmesi için mehir kavramının kanunlar ihtilafı kurallarına göre vasıflandırılması gerekir. Bu makalede öncelikle mehir kavramı açıklamakta ve devamında evliliğin genel hükümlerinin mehrin vasıflandırılmasındaki yer tartışılmaktadır.
Keywords: Sosyal ve Beşeri Bilimler; Hukuk; Devletler Özel Hukuku; Social Sciences and Humanities; Law; International Private Law; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; HUKUK; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; LAW; Hukuk; Sosyal Bilimler ve Beşeri Bilimler; Social Sciences & Humanities